1999
DOI: 10.1002/biof.5520090108
|View full text |Cite
|
Sign up to set email alerts
|

13‐HPODE and 13‐HODE modulate cytokine‐induced expression of endothelial cell adhesion molecules differently

Abstract: Expression of cellular adhesion molecules (CAMs) at endothelial surfaces represents a physiological response to vascular damage and mediates the initiation of inflammation and possibly of atherogenesis. The cytokines TNF alpha and IL-1 are potent inducers of CAMs in endothelial cells. Reactive oxygen species comprising lipid oxidation products have been implicated in the signaling pathways of both TNF alpha and IL-1 and accordingly could modulate atherogenic events. We, therefore, investigated the potential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Also, we demonstrated that exposure of rat endothelial cells to ARA did not alter the expression of the adhesion molecules VCAM-1 and ICAM-1 (data not shown). Several studies also reported that OXLAMs could promote inflammation by modulating proinflammatory cytokines IL-1β and TNF-α levels through the NF-κB pathway [25,71,75,76]. In humans, Ramsden et al [36] showed that lowering dietary LA reduces plasma OXLAMs levels reinforcing the direct link between LA and its circulating oxidized metabolites.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Also, we demonstrated that exposure of rat endothelial cells to ARA did not alter the expression of the adhesion molecules VCAM-1 and ICAM-1 (data not shown). Several studies also reported that OXLAMs could promote inflammation by modulating proinflammatory cytokines IL-1β and TNF-α levels through the NF-κB pathway [25,71,75,76]. In humans, Ramsden et al [36] showed that lowering dietary LA reduces plasma OXLAMs levels reinforcing the direct link between LA and its circulating oxidized metabolites.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…In atherosclerotic lesions, hydroperoxides as well as the 15-lipoxygenase were found (Ylä-Herttuala, 1991), and lipid hydroperoxides can induce adhesion molecules in cultivated endothelium cells (Friedrichs et al, 1999). Both oxLDL-induced foam cell formation and smooth muscle cell proliferation and hydroperoxide-induced presentation of adhesion molecules are considered to synergize in the initiation of atherogenesis.…”
Section: Selenium and Atherogenesismentioning
confidence: 99%
“…In addition, lipid hydroperoxidederived short-chain aldehydes, such as 4-hydroxy-2-nonenal (HNE), are reported to modulate proatherogenic responses (22). Lysophosphatidylcholine (LysoPC) and hydro(pero)xy fatty acids, such as hydro(pero)xyoctadecadienoic acid [H(p)ODE] and hydro(pero)xyeicosatetraenoic acid [H(p)ETE], have been reported to induce expression of cell adhesion molecules in endothelial cells (23)(24)(25). LysoPC and hydro(pero)xy fatty acids might be generated in atherosclerotic lesions by certain phospholipase A 2 (PLA 2 ) enzymes (26,27).…”
mentioning
confidence: 99%